Similar earthquake swarms in the trace of southern Tibetan grabens reveal a subtle strain transient event along the Main Himalayan Thrust - Bollinger, L; Rajaure, S; Sapkota, SN (Journal of Nepal Geological Society, 2008)
From December 1996 to February 1997 the Nepal Seismological Centre (NSC) recorded a simultaneous dramatic increase in midcrustal seismicity rates in 3 distinct regions, hundred of kilometers from each other, along the Main Himalayan Thrust (MHT). Although the rate of seismic events and their magnitudes differ between clusters, the 3 swarms normalized time structures appear very similar, including a pre-swarm decrease in event rate. Furthermore, two swarms appear weeks before their main shock events. Strikingly, the three regions affected are located in the trace of Southern Tibetan grabens inclined, a few months later, to large seismic crisis. The likelihood of three swarms occurring simultaneously, and depicting the same time structure, by chance alone, is tested. Its probability, determined using different approaches, is small. The events may be related to a single process. A subtle transient slip event along the deeper part of the seismogenic zone of the Main Himalayan Thrust is therefore suspected. However, the seismicity rate change between the clusters appears insignificant. We describe the stress pattern along the high Himalayan range in Nepal, and show that the 3 regions affected by the swarms appear more sensitive than others to small stress changes. Continuous Everest DORIS station as well as sparse campaign GPS data allow put an upper bound to this subtle strain transient event. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.3